PEMANFAATAN FILTRAT DAUN MUDA JATI SEBAGAI BAHAN PEWARNA ALTERNATIF DALAM PEMBUATAN PREPARAT JARINGAN TUMBUHAN - MITA NURWANTI (Program Studi Pendidikan Biologi, FMIPA, Universitas Negeri Surabaya, 2013)
Preparations of plant tissue is not owned by some schools because the price is relatively expensive and to make themselves constrained chemical dyes prices are expensive. Therefore we need an alternative dye that is more affordable and can be made for making permanent preparations of plant tissue the dye from the filtrate young leaves of teak (Tectona grandis). This study aims to develop a natural vegetable dyes from the filtrate young teak leaves to stain the tissue in the process of making preparations of plant tissue. Type of research is a study development. Natural dye-making research procedures by making young teak leaf filtrate diluted with alcohol. Making preparations of plant tissue using free slices of monocotyledonous and dicotyledonous roots and stems with dyeing of the young leaves filtrate teak. The results of this research are dyeing of the filtrate young teak leaves can stain the tissue epidermis, parenchyma, phloem, xylem and sklerenkim well on plant tissue preparations were developed. Keywords: dyeing of the young leaves filtrate teak (Tectona grandis), preparation of plant tissue.